Together towards new life for missiology? Mission and missiology in the light of the World Council of Churches 2013 policy statement - C. J. P. Niemandt (Acta Theologica)
Any meaningful discussion of the various understandings of mission and Missiology needs to take cognizance of the important policy document accepted by the World Council of Churches at its 10th Assembly in Busan, South-Korea, in October 2013: “Together towards life – mission and evangelism in changing landscapes”. This is the first new mission affirmation by the WCC in 30 years,  and presents a compelling new vision of Christian mission, namely its rootedness in God and its present role in the strengthening/consolidation/reinforcement of the reign of God. This research explores the relevance of the aforementioned policy document for mission and Missiology in terms of three themes: “Where do we come from?”; “What is happening now?”, and “What could the future look like?”